Pemanfaatan Tanah Gambut Sebagai Bahan Campuran Tanah Laterit Ditinjau Dari Nilai CBR (California Bearing Ratio) - Hesar, Annisa Fitria; Saputri, Anzeli; Rafani, Muhammad; Wattini, Wattini (Politeknik Negeri Jakarta, 2025)
West Kalimantan, particularly the city of Pontianak, is known for its abundant peat soil reserves. Peat soil forms from the accumulation of organic material derived from decomposed vegetation under water-saturated conditions. In construction, the use of local materials such as peat soil can be a strategic alternative to reduce project costs and minimize environmental impact. In this study, peat soil was utilized as an additive in laterite soil mixtures intended for subgrade applications. The purpose of using peat is to reduce construction costs and minimize negative environmental impacts. This research aims to determine the effect of varying peat content—10%, 20%, 30%, 40%, and 50%—on the California Bearing Ratio (CBR) of laterite soil. The results show that the CBR value of natural laterite soil is 32.69%. When mixed with 10% peat, the CBR decreases to 12.53%; at 20%, it drops to 10.25%; at 30%, it further reduces to 6.8%; and at 40%, it falls to 4.56%. For mixtures containing 50% or more peat, no measurable CBR value was obtained. These findings indicate a significant reduction in bearing capacity as peat content increases.